17. Evaluation of MR and PET compatibility of dedicated radiotherapy positioning devices – a preliminary study. (December 2018) - Zorz, A.; Gianelli, M.; Scaggion, A.; Fusella, M.; Branchini, M.; Turco, P.; Capotosto, A.; Zucchetta, P.; Paiusco, M.
Abstract : Purpose: The aim of this preliminary study was to assess the compatibility of dedicated positioning devices developed for MR/PET imaging integration into radiotherapy planning. Methods: The X-Tend Flat Table Top and specifically designed radiofrequency coil holders were tested on an integrated Biograph mMR MR/PET scanner (Siemens Healthcare). Magnetic field homogeneity and MR image quality in terms of artifacts and signal-to-noise ratio (SNR), with and without the radiotherapy positioning devices, were evaluated by means of a field sequence with 0.1 ppm/line and a clinical T2-weighted sequence, respectively. Acquisitions of a cylindrical (diameter 16 cm) doped (NiSO4 ) water phantom were performed by using a flexible 8-channel radiofrequency coil. SNR was estimated through the subtraction method. Since glass fiber table top and radiofrequency coil holders can attenuate PET signal, introducing potential quantification errors, PET photon attenuation was tested by the use of a cylindrical uniform phantom filled with 18-F and a sealed 68-Ge phantom. Also, a CT scan of the equipment was performed to calculate the transmission factor at 511 keV. Results: The use of the dedicated radiotherapy positioning devices did not affect appreciably magnetic field homogeneity, and did not yield evident artifacts in T2-weighted images. When using the radiotherapy devices, SNR showed a reduction of less than 5% with respect to standard MR acquisitions. The average transmission factor of the radiotherapy table was computed to be around 90% from both CT scan and PET photon attenuation. Conclusions: Based on our preliminary results, the dedicated radiotherapy positioning devices seem to be MR and PET compatible. Effect of radiotherapy devices on MR geometrical distortion and image uniformity, also for non-conventional quantitative diffusion-weighted imaging (a useful and sensitive tool for oncologic applications), are under evaluation. Further investigation is needed to assess the effect of radiotherapy table attenuation on PET contrast of lesions.